MEMBENTUK KELUARGA TERAMPIL DALAM KESEHATAN REPRODUKSI REMAJA DENGAN PROGRAM PENGUATAN KELUARGA - Maurida, Nurul; Ali Basri, Achmad; Angelia Silvanasari, Irwina; Vitaliati, Trisna; Wariin, Sulton (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2026)
Families play a role in improving adolescent reproductive health and preventing problems. The objective of this program is to improve family skills in optimizing adolescent reproductive health through a family strengthening program. The program partners were 20 families with adolescents, consisting of fathers, mothers, and their adolescent children. The program method was a family strengthening program consisting of three meetings. The results of the program showed that before the family strengthening program was implemented, the majority of families communication skills with their adolescent children were in the poor category (82%), the majority of families skills in personal genital hygiene were in the poor category (86%), and the majority of adolescents skills in fulfilling balanced nutritional needs were in the poor category (72%). After the family strengthening program, the majority of families communication skills with their adolescent children were in the good category (64%), the majority of families skills in personal genital hygiene were in the good category (73%), and the majority of adolescents' skills in fulfilling balanced nutritional needs were in the good category (67%). This proves that the family strengthening program is able to improve family skills in optimizing adolescent reproductive health through communication skills in adolescents, personal genital hygiene skills, and skills in fulfilling balanced nutritional needs in adolescents